Proses Morfofonemik Pembentukan Kata Berkonfiks dalam Bahasa Minangkabau - Rahayu, Zona Rida (ppjbsip, 2025)
This study aims to explain the morphophonemic process of word formation with confixes in the Minangkabau language. The study uses a qualitative ethnographic approach with a descriptive method. Data were obtained from direct speech by women in Bakureh activities in Solok City, Lubuk Sikarah District, through in-depth observation and participatory interviews supported by recordings and field notes. The validity of the data was tested using triangulation techniques. The results of the study indicate that confixes are simultaneous, namely affixes are attached simultaneously to the base word, so that the separation of one element results in a meaningless form. The morphophonemic process includes (a) consonant melting, such as /s/ and /h/ become /ny/ or disappear, /k/ becomes /ng/, /p/ becomes /m/, and /t/ becomes /n/; (b) variations in the prefix paN- which changes to pan-, pam-, pany-, pang-, and par- according to the initial phoneme of the base word; and (c) maintenance of phonological structure without significant phonemic changes. Minangkabau confixes are productive because they can be attached to various word classes and produce a variety of grammatical meanings. This finding contributes to the documentation of Minangkabau vocabulary as part of regional language preservation. AbstrakPenelitian ini bertujuan menjelaskan proses morfofonemik pembentukan kata berkonfiks dalam bahasa Minangkabau. Penelitian menggunakan pendekatan kualitatif etnografis dengan metode deskriptif. Data diperoleh dari tuturan langsung perempuan dalam kegiatan Bakureh di Kota Solok, Kecamatan Lubuk Sikarah, melalui observasi mendalam dan wawancara terlibat yang didukung perekaman serta catatan lapangan. Keabsahan data diuji menggunakan teknik triangulasi. Hasil penelitian menunjukkan bahwa konfiks bersifat simultan, yakni afiks melekat secara serentak pada kata dasar, sehingga pemisahan salah satu unsur menghasilkan bentuk tidak bermakna. Proses morfofonemik meliputi (a) peluluhan konsonan, seperti /s/ dan /h/ menjadi /ny/ atau hilang, /k/ menjadi /ng/, /p/ menjadi /m/, serta /t/ menjadi /n/; (b) variasi prefiks paN- yang berubah menjadi pan-, pam-, pany-, pang-, dan par- sesuai fonem awal kata dasar; dan (c) pemertahanan struktur fonologis tanpa perubahan fonemik yang signifikan. Konfiks bahasa Minangkabau bersifat produktif karena dapat melekat pada berbagai kelas kata dan menghasilkan keragaman makna gramatikal. Temuan ini berkontribusi pada pendokumentasian kosakata bahasa Minangkabau sebagai bagian dari pelestarian bahasa daerah.